Conductivity and Flexibility Enhancement of Aerosol-Jet-Printed Sensors Using a Silver Nanoparticle Ink with Carbon Nanotubes - Haining Zhang; Seung Ki Moon; Min-Kyo Jung; Pil-Ho Lee; Taeho Ha (Archives of Metallurgy and Materials)
Efforts to miniaturize and customize electronic devices have attracted considerable amounts of attention in many industrial fields. Recently, due to its innovative printing technology with the capability of printing fine features onto non-planar substrates without masks, aerosol jet printing (AJP) is emerging as a promising printed-electronics technology capable of meeting the requirements of various advanced electronic applications. In this research, a novel manufacturing process based on AJP is proposed in order to fabricate highly flexible and conductive customized temperature sensors. To improve the flexibility and conductivity of the printed tracks, a silver nanoparticle/carbon nanotubes composite ink is developed. Customized temperature sensors are then designed and fabricated based on the optimized process parameters of AJP. It was found that the CNTs served as bridges to connect silver nanoparticles and defects, which could be expected to reduce the contact resistivity and enhance the flexibility of the printed sensor.